Nano-KTN@Ag/PVDF composite films with high permittivity and low dielectric loss by introduction of designed KTN/Ag core/shell nanoparticles. Issue 34 (16th August 2016) - Chen, Gaoru; Wang, Xuan; Lin, Jiaqi; Yang, Wenlong; Li, Haidong; Wen, Yinian; Li, Landi; Jiang, Zhichao; Lei, Qingquan
Abstract : Nano-KTN with an intrinsic dipole moment was used as a nucleus, which makes Ag shells generate induced polarization to enhance the polarizability in the composites. Abstract : A designed nano-KTN/Ag core/shell structure endows nano-KTN@Ag/PVDF composite films with excellent properties of remarkably enhanced dielectric permittivity, low loss tangent and flexibility. It has been found that the incorporation of KTN@Ag nanoparticles can increase the average crystallite size of the β phase in a polymer matrix, which elevates the polarization level of the polymer matrix and increases the dielectric permittivity of the nanocomposites. 25 vol% composites own a remarkably enhanced dielectric permittivity ( ε r = 230) at 100 Hz, which is due to MWS polarization at the internal interface between nano-KTN@Ag and the PVDF matrix, the increased induced polarization of the nanoparticles and the "boundary layer capacitor effect". The low loss tangent is achieved because of an enhanced polarization reverse speed by the Ag shells and a blockage of charge transfer by PVDF chains. The percolation threshold of the composite films ( f c = 0.317) was predicted by the percolation theory, and the theoretical results were in good agreement with the experimental data.